(untitled) (Research, Society and Development, 2021)
Introduction: Facial traumas correspond to all injuries of traumatic origin that affect the facial mass and are generally related to high rates of morbidity, loss of function and high aesthetic and social costs. Objective: to understand the facial trauma caused by physical aggressions and what are their implications in the life of the affected person. Methods: Exploratory and descriptive study based on a literature review based on the last 25 years on studies available online (PubMed, MEDLINE, SciELO and LILACS). The descriptors in English were used: Facial injuries, Violence, Aggression and Dentistry, thus a total of 247 studies were found, of which 36 comprised the present research. Results: Facial injuries are among the most frequent diagnoses in a general emergency room, and as a result, they have become an inevitable issue for health professionals. Its increase in recent decades is a result of the growth of violence in cities. Of the types of violence, physical aggression seems to be the most common cause and a significant increase in the prevalence of facial trauma resulting from interpersonal violence (which may be over 50%) has been reported. Conclusion: The complications of facial trauma are complex, and may compromise the physical, aesthetic and psychological integrity of the affected person. There is a need for greater interest in public policies in the treatment of the creation of more trauma hospitals and social programs to reduce the rates that have been increasing considerably.